A new species of Usnea (Parmeliaceae, lichenized Ascomycota) from Southwest China - Han, Liu-Fu; Xie, Yu-Huan; Zhang, Huan-Bing; Li, Li-Si; Guo, Shou-Yu (Phytotaxa, 2020)
During the study of Usnea from China, we identified and illustrated a new species, Usnea sulphuridiscoidea S. Y. Guo & L. F. Han from the Ailaoshan Mountain of Southwest China, based on morphological characteristics and nrDNA ITS sequence data. This new species can be distinguished morphologically from other apotheciate members of Usnea by the special lateral apothecia with sulphur disc, the inflated branches with glossy surface and numerous papillae as well as many fibrils, meanwhile lacking pseudocyphellae and soralia. The nrDNA ITS sequence data supported the recognition of the new species.